Involvement of the eIF2α Kinase GCN2 in UV-B Responses - Llabata, Paula; Richter, Julia; Faus, Isabel; Słomiňska-Durdasiak, Karolina; Zeh, Lukas Hubert; Gadea, Jose; Hauser, Marie-Theres (Frontiers in Plant Science, 2019)
GCN2 (GENERAL CONTROL NONREPRESSED2) is a serine/threonine-protein kinase that regulates translation in response to stressors such as amino acid and purin deprivation, cold shock, wounding, cadmium and UV-C exposure. Activated GCN2 phosphorylates the α-subunit of the eukaryotic translation initiation factor 2 (eIF2) leading to a drastic inhibition of protein synthesis and shifting translation to specific mRNAs. To investigate the role of GCN2 in responses to UV-B radiation its activity was analyzed through eIF2α phosphorylation assays in mutants of the specific UV-B and stress signaling pathways of Arabidopsis thaliana. EIF2α phosphorylation was detectable 30 min after UV-B exposure, independent of the UV-B photoreceptor UV RESISTANCE LOCUS8 and its downstream signaling components. GCN2 dependent phosphorylation of eIF2α was also detectable in mutants of the stress related MAP kinases, MPK3 and MPK6 and their negative regulator MAP KINASE PHOSPHATASE1 (MKP1). Transcription of downstream components of the UV-B signaling pathway, the CHALCONE SYNTHASE (CHS) was constitutively higher in gcn2-1 compared to wildtype and further increased upon UV-B while GLUTATHIONE PEROXIDASE7 (GPX7) behaved similarly to wildtype. The UVR8 independent FAD-LINKED OXIDOREDUCTASE (FADox) had a lower basal expression in gcn2-1 which was increased upon UV-B. Since high fluence rates of UV-B induce DNA damage the expression of the RAS ASSOCIATED WITH DIABETES PROTEIN51 (RAD51) was quantified before and after UV-B. While the basal expression was similar to wildtype it was significantly less induced upon UV-B in the gcn2-1 mutant. This expression pattern correlates with the finding that gcn2 mutants develop less cyclobutane pyrimidine dimers (CPDs) after UV-B exposure. Quantification of translation with the puromycination assay revealed that gcn2 mutants have an increased rate of translation which was also higher upon UV-B. Growth of gcn2 mutants to chronic UV-B exposure support GCN2’s role as a negative regulator of UV-B responses. The elevated resistance of gcn2 mutants towards repeated UV-B exposure points to a critical role of GCN2 in the regulation of translation upon UV-B.